Development of Canadian governance and foreign policy, 1883-1904. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2011)
Gilbert John Elliot-Murray-Kynynmound (1845-1914), the Fourth Earl of Minto, was involved in Canadian governance in various roles between 1883 and 1905. He served as Canadian Military Secretary from 1883 and 1885 before becoming Governor-General from 1898 to 1905. This collection is drawn from his personal papers and offers a detailed account of the changing shape of governance and development in one of Britain's most important colonies. The files include material relating to rebellions by French-Canadians and indigenous peoples, the recruitment of Canadian troops for Britain's imperial wars, and questions of trade between Canada and the rest of the world. Additionally, the collection hosts a wealth of correspondence between Elliot-Murray-Kynynmound and important British political figures like Queen Victoria and Joseph Chamberlain. Thus, the collection offers an interesting portrait of colonial governance, constitutional politics, and national security in Canada.
Date range: 1883-1904.
Keywords: Minto, Gilbert John Murray Kynynmond Elliot, -- Earl of, -- 1845-1914.; Canada -- Politics and government -- 1867-1914.; Heads of state -- Canada -- Biography